Estimation of aeroelastic stability of a tower spire - A. M. Belostotsky; I. Yu. Negrozova; O. S. Goryachevsky (Vestnik MGSU)
Introduction. Large-span and flexible structures are very sensitive to the effects of wind. Such structures are subject to the occurrence of aeroelastic phenomena. In history there are known cases when as a result of wind impact, there was a collapse of the structure. In this regard, the development of methods for estimation of aeroelastic instability is an urgent task.Materials and methods. Dynamic and stiffness characteristics of the object, used in engineering assessment of the possibility of aeroelastic phenomena, were determined using the ANSYS Mechanical software package. Modelling of the flow around the object under study was carried out using the ANSYS Fluent software package. To confirm the obtained estimates of the impossibility of the occurrence of aeroelastic instability according to the normative method, direct numerical simulation of the two-sided interaction between the spire and the air flow was carried out in the ANSYS software (two-way FSI, implemented by a combination of Fluent and Mechanical modules).Results. Using the developed computational dynamic finite element models, natural frequencies and vibration modes are determined. An assessment of the possibility of galloping occurrence was carried out according to the normative method for the studied spire at velocity observed at the construction site. Direct numerical modelling of the coupled problem of two-sided interaction between the spire and the air flow was carried out in the ANSYS software package at the maximum possible wind speed for the construction site for the most dangerous wind direction (obtained from the results of engineering assessment).Conclusions. The assessment of the possibility of aeroelastic instability according to the normative methodology and verification two-sided coupled calculation of aeroelastic oscillations of the spire confirmed the absence of aeroelastic instability phenomena at the maximum possible wind speed for the construction site.